MICRORNA-26 REGULATES RAT CARDIAC REMODELLING BY SUPPRESSING GLYCOGEN SYNTHASE KINASE 3β. (8th October 2012) - Zhang, Zhenhui; Liu, Benrong; Luo, Chengfeng; Zhong, Yun; Chen, Weiyan; Li, Aiqun; Chen, Minsheng; Liu, Shiming; Liu, Shiming
Abstract : Objectives: MicroRNA-26 (miR-26) was found to be down-regulated in the myocardium in cardiac remodelling animal models. Here we investigated the critical role of miR-26a/b on cardiac remodelling in vivo and in vitro. Methods: Rats which underwent sham or transverse abdominal aortic constriction (TAAC) surgery were divided into control and TAAC group. Cardiomyocytes (CMs) and cardiac fibroblasts (CFs) were isolated from neonatal Sprague-Dawley rats. QPCR assay was applied to detect the expression levels of miR-26 a/b in the myocardial tissue and plasma of TAAC rats, and in CMs and CFs treated with angiotesinII(AngII). Gain- and loss-of-function studies were applied through overexpressing or inhibiting miR26a/b or Glycogen Synthase Kinase 3β (GSK3β) by liposomes transfecting. Results: The data demonstrated that the expressive levels of miR-26a/b were down-regulated in cardiac tissues and plasma in TAAC rats, moreover in CMs and CFs treated with AngII. Furthermore, overexpression miR26a/b by transfected miR-26a/b mimics in CM or CF inhibited CM hypertrophy or CF collagen synthesis significantly, and down-regulating the expressive levels of miR-26a/b by transfected miR-26a/b inhibitors in CM or CF led to opposite effects, suggesting that miR-26 was an anti-hypertrophy and anti-fibrosis gene. Through luciferase assay our study suggested that Glycogen Synthase Kinase 3β (GSK3β) gene that was negatively regulated by miR-26 in CM and CF may be a direct target of miR-26. Overexpression of miR-26 attenuates the endogenous GSK3β mRNA and protein levels followed by the inhibition of CM hypertrophy and CF collagen synthesis. Down-regulation of miR-26 reversed these effects. Furthermore, silence of GSK3β gene phenocopied the anti-hypertrophy and anti-fibrosis effects of miR-26, whereas overexpression of this protein attenuated the effects of miR-26. Conclusions: Our data highlight an important role of miR-26 in the control of pathological structural changes in rat heart, which may associated with suppressing the GSK3β signalling pathway, and implicate the potential application of miR-26 in diagnosis and therapy of cardiac remodelling.